2004
DOI: 10.1590/s0034-89102004000500003
|View full text |Cite
|
Sign up to set email alerts
|

A cor da morte: causas de óbito segundo características de raça no Estado de São Paulo, 1999 a 2001

Abstract: ObjectiveAssuming that ethnicity might be a basis for social differentiation and that such differences might represent vulnerability to sickness, this study attempts to verify whether race or ethnic origin have an effect on mortality patterns. MethodsThe Sao Paulo State death register was examined from 1999 to 2001 in a contingence table of causes according to the 10 th ICD and race or skin-color categories (White, Black, Mulatto and others). Chi-square test was used to check the association between skin-color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
60

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 2 publications
1
31
0
60
Order By: Relevance
“…The study conducted by the Batista, Escuder and Pereira (2004) found that, proportionally, in the State of São Paulo, black and brown people die more than white people for mental disorders. Barros et al (2014) identified a higher proportion of black population (black and brown people) hospitalized in psychiatric hospitals of the state of São Paulo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study conducted by the Batista, Escuder and Pereira (2004) found that, proportionally, in the State of São Paulo, black and brown people die more than white people for mental disorders. Barros et al (2014) identified a higher proportion of black population (black and brown people) hospitalized in psychiatric hospitals of the state of São Paulo.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of racism on health, illness and death has been discussed by several authors, of which we highlight Araújo et al (2009);Araújo et al (2012); Barbosa (1998);Batista;Escuder;Pereira (2004) and Lopes (2005).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Os negros (pretos e pardos) predominaram em todos os tipos de ocorrência, principalmente entre as violências, em conformidade com panorama nacional de morbimortalidade por causas externas 7,25,26 . Diferenças étnicas associam-se a desigualdades sociais e condicionam a forma de viver e de morrer de grupos de pessoas.…”
Section: Discussão E Considerações Finaisunclassified
“…There is already a considerable volume of evidence indicating a systematic condition of disadvantage and exclusion among black and brown (pardo) individuals, in relation to whites, covering various periods during the course of life. 3 However, investigations on ethnic-racial inequalities have come up against methodological problems. Discussions on the validity and reliability of measuring the variable "race" have taken place within different fi elds of knowledge, such as genetics 18 and public health.…”
Section: Introductionmentioning
confidence: 99%